2023
DOI: 10.1002/adfm.202312651
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in Antimicrobial Bottle Brush Copolymers and Its Influence on Biological Activity

Anne‐Catherine Lehnen,
Sergio Kogikoski,
Till Stensitzki
et al.

Abstract: Antimicrobial polymers are a promising alternative to conventional antibiotics in the fight against antimicrobial resistance. Cationic bottle brush copolymers have shown to be superior to linear topologies in previous studies. Herein, the aspect ratio of such polymers is varied creating differently shaped confined unimolecular structures with varying degrees of side chain mobility. Using reversible addition‐fragmentation chain‐transfer (RAFT) polymerization, bottle brushes are produced in a one‐pot procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…However, it should be noted that in the present study, grafts are substantially longer. As we have also shown that the degree of freedom of side chains has a severe impact on bioactivity, 46 a direct comparison might not be overly meaningful. Another difference lies in the selectivity between the bacteria strains.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it should be noted that in the present study, grafts are substantially longer. As we have also shown that the degree of freedom of side chains has a severe impact on bioactivity, 46 a direct comparison might not be overly meaningful. Another difference lies in the selectivity between the bacteria strains.…”
Section: ■ Introductionmentioning
confidence: 97%
“…In our previous work, we have demonstrated how crucial the shape and anisotropy of antimicrobial polymers is on a molecular level. 46,47 The limited and modulated hydrophobicity of these systems based on N-isopropylacrylamide (NIPAM) and amino ethyl acrylamide (AEAM) leads to impressive selectivities. Thus, we aimed to probe if these polymers can be applied as a component in antimicrobial nanostructures via CDSA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Here, a slightly acidic p K a -value of the polymeric amine is desirable in order to promote endosomal membrane interaction under acidic conditions, but at the same time to minimize interactions with the cytoplasmic membrane to improve the compatibility of the polycations . This high membrane interaction further renders them suitable for applications as antimicrobial polymers. , …”
Section: Introductionmentioning
confidence: 99%
“… 10 This high membrane interaction further renders them suitable for applications as antimicrobial polymers. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%